Hypnosis as neurophenomenology - Lifshitz, Michael; Cusumano, Emma P.; Raz, Amir (Frontiers in Human Neuroscience, 2013)
Hypnosis research binds phenomenology and neuroscience. Here we show how recent evidence probing the impact of hypnosis and suggestion can inform and advance a neurophenomenological approach. In contrast to meditative practices that involve lengthy and intensive training, hypnosis induces profound alterations in subjective experience following just a few words of suggestion. Individuals highly responsive to hypnosis can quickly and effortlessly manifest atypical conscious experiences as well as override deeply entrenched processes. These capacities open new avenues for suspending habitual modes of attention and achieving refined states of meta-awareness. Furthermore, hypnosis research sheds light on the effects of suggestion, expectation, and interpersonal factors beyond the narrow context of hypnotic procedures. Such knowledge may help to further foster phenomenological interviewing methods, improve experiential reports, and elucidate the mechanisms of contemplative practices. Incorporating hypnosis and suggestion into the broader landscape of neurophenomenology, therefore, would likely help bridge subjective experience and third-person approaches to the mind.